In-vivo antimalarial activity of Holothuria scabra simplicia in Plasmodium berghei-infected mice - Sri Laksemi, Dewa Ayu Agus; Asri Damayanti, Putu Ayu; Sudarmaja, I Made; Tunas, I Ketut; Ratna Sundari, Luh Putu; Rustini, Ni Luh; Budi Apsari, Putu Indah (Faculty of Medicine, Universitas Trisakti, 2024)
BACKGROUNDMalaria remains one of the major causes of death worldwide. Holothuria scabra has a high nutritional content and many biological effects. The development of alternative anti-malarial drugs is necessary, considering that resistance to the newest anti-malarial drugs has been reported. This research study aimed to determine the anti-malarial effects of Holothuria scabra in mice infected with Plasmodium berghei. METHODSThis was a post-test only control group study conducted on 24 Balb/c mice. Peter’s four-day suppressive test was employed to ascertain the claimed anti-plasmodial effect of the simplicia. Following inoculation with P. berghei, all 24 mice were infected and randomized into 4 groups, namely 3 treatment groups and 1 control group. The control group was given carboxymethyl cellulose, two of the treatment groups were given doses of 10 and 100 mg/kg BW Holothuria scabra, respectively, using Peter’s four-day suppressive test, while the remaining treatment group received a dose of 100 mg/kgBW using the prophylactic method. Data were analyzed using One way ANOVA. RESULTSThe results showed by using both the four-day suppressive test and the prophylactic method, that Holothuria scabra has antimalarial activity. Holothuria scabra at a dose of 100 mg/kg BW was significantly effective in decreasing the percentage of parasitemia (p=0.000) and tended to inhibit the growth of Plasmodium berghei in mice (p=0.054). CONCLUSIONThis study demonstrated that Holothuria scabra possesses anti-plasmodial activity in mice. Hence, the sea cucumber could serve as a potential source of a newer antimalarial agent.